Management accounting systems: an organizational competitive performance perspective - Pedroso, Elsa (2020)
STRUCTURED ABSTRACT Purpose – The purpose of this paper is to explore the impact of the characteristics and roles of management accounting systems (MAS) on today’s business organizations and their management, systems, procedures, people, performance, and competitive environments. Design/methodology/approach – A survey-based methodology was utilized in this research to gather organizational information relevant to the different facets of the MAS and their operational and strategic practices impact on organizations operating under increasingly uncertain and competitive environments. A structural equation modeling approach was utilized to uncover relevant relationships and associations among relevant variables. Findings – The findings of this exploratory research revealed a direct influence of MAS on the managerial and organizational performance through the managers’ performance. The results also suggest that MAS is directly influenced by users’ training, and satisfaction, task uncertainty, and decentralization of decisions. It was also indirectly influenced by top management support. In addition, the findings also revealed a direct influence of the decentralization of decisions on the managers’ and on organizational performance. Research limitations/implications – While this study addressed important issues that have practical management value, it is limited to a sample from one country. Future studies in different businesses and cultural settings are needed to enhance the theoretical and practical contributions of the findings and conclusions of this study. Practical implications – The issues explored in this study are very much relevant to the utilization and design of MAS and their increasing tactical and strategic roles in the management of today’s business organizations. The findings of this study have relevant practical value for managers as they attempt to cope with increasingly competitive environments through the deployment of their existing capabilities and best practices. In this context, the accounting management system has practical utilities that facilitate the control and management of the operations and strategies of the organization. Originality/value – This research offers practicing management an integrated approach, as they aspire to utilize their organizational MAS to increase the efficiency and effectiveness of their organizations. Integrating the different aspects of management accounting information systems, given their impact on the different aspects of the organization, is needed for the establishment of theoretical research models aiming at the enhancement of the competitive performance of today’s organizations. This study also offers to executives of SMEs a new multidimensional instrument for assessing the effectiveness of their management information systems, which can help to improve their benchmarking processes.